Strong, stretchable and ultrasensitive MWCNT/TPU nanocomposites for piezoresistive strain sensing. (15th November 2019) - Kumar, S.; Gupta, Tejendra K.; Varadarajan, K.M.
Abstract: We report strong, stretchable and ultrasensitive thermoplastic polyurethane (TPU) nanocomposites reinforced with multiwalled carbon nanotubes (MWCNT) for piezoresistive strain sensing. Uniform dispersion of MWCNT in TPU matrix offers low percolation threshold (0.1 wt%) and superior electrical conductivity. MWCNT/TPU nanocomposites exhibit different sensitivities and measurable strain ranges depending upon MWCNT concentration. Static stretch experiments reveal nearly linear piezoresistive response up to 15%, 35% and 45% strain with gauge factor (GF) of 22, 8.3 and 7.0 for 0.3, 0.5 and 1.0 wt% MWCNT loaded TPU nanocomposites, respectively. With further stretching, TPU nanocomposites evince strain-dependent GF of 6395, 6423 and 7935 at 35%, 95% and 185% strain for 0.3, 0.5 and 1.0 wt% MWCNT loading, respectively. Furthermore, we observe improvements in tensile strength, yield strength and Young's modulus of 51%, 37% and 23% for 0.1 wt % MWCNT loading and 10%, 83% and 66% for 0.3 wt % MWCNT loading, respectively. Cyclic stretch/release tests for 0.3 wt% MWCNT loaded nanocomposites show good recoverability and reproducibility over 100 cycles up to a strain-amplitude of 50%. Ultrahigh GF of MWCNT/TPU nanocomposites compared to extant work together with their tuneable sensitivity in both small and large strain regimes, enhanced strength and ease of fabrication make them attractive for high performance strain sensing devices. Graphical abstract: Image 1